Transcendental Self and the Feeling of Existence - Kumar, Apaar (Con-Textos Kantianos. International Journal of Philosophy, 2016)
In this essay, I investigate one aspect of Kant’s larger theory of the transcendental self. In the Prolegomena, Kant says that the transcendental self can be represented as a feeling of existence. In contrast to the view that Kant errs in describing the transcendental self in this fashion, I show that there exists a strand in Kant’s philosophy that permits us to interpret the representation of the transcendental self as a feeling of existence—as the obscurely conscious and temporally inaccessible modification of the state of the discursive subject, which is built into all the representations of such a subject. I also provide an account of how the transcendental self can be legitimately understood both as an epistemic condition for the possibility of experience as well as the representation of a non-naturalistic feeling of existence.